Noninvasive Pulmonary Hemodynamic Evaluation in Athletes With Exercise-Induced Hypoxemia - Durand, Fabienne; Gaston, Anne-Fleur; Vicenzi, Marco; Deboeck, Gael; Subirats, Enric; Faoro, Vitalie (Chest, 2020)
Pulmonary capillary stress failure is potentially involved in exercise-induced hypoxemia (ie, a significant fall in hemoglobin oxygen saturation [Spo2]) during sea level exercise in endurance-trained athletes. It is unknown whether there are specific properties of pulmonary vascular function in athletes exhibiting oxygen desaturation. Ten endurance-trained athletes with exercise-induced hypoxemia (EIH), nine endurance-trained athletes with no exercise-induced hypoxemia (NEIH), and 10 untrained control subjects underwent an incremental exercise stress echocardiography coupled with lung diffusion capacity for carbon monoxide (Dlco) and lung diffusion capacity for nitric oxide (Dlno) testing. Functional adaptation of the pulmonary circulation was evaluated with measurements of mean pulmonary arterial pressure (mPAP), pulmonary capillary pressure, pulmonary vascular resistance (PVR), cardiac output (Qc), and pulmonary vascular distensibility (alpha) mathematically determined from the curvilinearity of the multi-point mPAP/Qc relation. EIH athletes exhibited a lower exercise-induced PVR decrease compared with the untrained and NEIH groups (P < .001). EIH athletes showed higher maximal mPAP compared with NEIH athletes (45.4 ± 0.9 mm Hg vs 41.6 ± 0.9 mm Hg, respectively; P = .003); there was no difference between the NEIH and untrained subjects. Alpha was lower in the EIH group compared with the NEIH group (P < .05). Maximal mPAP, Pcap, and alpha were correlated with the fall of Spo2 during exercise (P < .01, P < .01, and P < .05). Dlno and Dlco increased with exercise in all groups, with no differences between groups. Dlno/Qc was correlated to the exercise-induced Spo2 changes (P < .05). EIH athletes exhibit higher maximal pulmonary vascular pressures, lower vascular distensibility, or exercise-induced changes in PVR compared with NEIH subjects, in keeping with pulmonary capillary stress failure or intrapulmonary shunting hypotheses.